Unity through culture - Suhr, Christian; Otto, Ton 1953- (Documentary Educational Resources, 2011)
"Soanin Kilangit is determined to unite the people and attract international tourism through the revival of culture on Baluan Island in the South Pacific. He organizes the largest cultural festival ever held on the island. But some traditional leaders argue that Baluan never had culture. Culture comes from the white man and is now destroying their old tradition. Others, however, take the festival as a welcome opportunity to revolt against '70 years of cultural oppression' by Christianity. A struggle to define the past, present and future of Baluan culture erupts to the sound of thundering log drum rhythms."-- Container
DVD ; all regions ; NTSC; Dolby digital 2.0
With: Soanin Kilangit, John Malai, Pokowei Pwaril, Otto Narumbuai, Sapulai Papi, Awai Salkimut, Sakumai Yep
Camera and sound, Christian Suhr, Steffen Dalsgaard
Keywords: Balopa Cultural Festival / (Baluan Island, Papua New Guinea); Culture and tourism / Papua New Guinea / Baluan Island; Heritage tourism / Papua New Guinea / Baluan Island; Manners and customs; Alltag, Brauchtum; Baluan Island (Papua New Guinea) / Social life and customs; DVD-Video